Case Series: Dystonia with multiple sclerosis and neuromyelitis optica - Hwang, Helen; Levasseur, Victoria A.; Perlmutter, Joel S. (Dystonia, 2023)
Dystonia is an uncommon complication of relapsing-remitting multiple sclerosis (MS) and related disorders. The types of dystonia described associated with MS are heterogenous, and the relationship between dystonia and MS remains unclear. Moreover, the anatomical correspondence between MS lesions and the site of dystonia has not been determined. Onset, treatment response, and outcomes of dystonia associated with MS still remain largely uncharacterized. Here, we report a case series of 14 patients with dystonia affecting different body parts in people with MS and neuromyelitis optica (NMO). We characterize the brain regions associated with this form of secondary dystonia and the response to botulinum toxin injections.